Results of treatment with topical mitomycin C 0.02% following excision of primary pterygium. Issue 3 (March 1995) - Rachmiel, R; Leiba, H; Levartovsky, S
Abstract : AIMS–The effectiveness of instillation of mitomycin C eyedrops on the recurrence rate of pterygium was assessed in patients undergoing primary pterygium surgery. Any side effects were also noted. METHODS–Primary pterygia in 38 consecutive patients were surgically excised during July to December 1992. After surgery, mitomycin C 0.02% eyedrops twice daily for 5 days as well as dexamethasone 0.1% four times tapered for the next 6 weeks were instilled. Postoperative follow up ranged from 6 to 11 months. RESULTS–In one patient the pterygium recurred after 3 months (recurrence rate 2.6%). The side effects encountered were: avascularised sclera in 13 cases between 1-10 months postoperatively; ocular discomfort and lacrimation in five cases; superficial punctate keratitis during the first month in three cases; pyogenic granuloma in two cases. In one patient steroid induced increased intraocular pressure was found 4 weeks after surgery. The adverse side effects were all mild, self limiting, and easily treated. CONCLUSION–This study suggests that postoperative instillation of mitomycin C 0.02% eyedrops twice daily for 5 days following excision of primary pterygium is an effective and safe treatment to obviate pterygium recurrence.